Buprenorphine withdrawal induced takotsubo cardiomyopathy: A series of unfortunate events. Issue 5 (May 2022) - Laina, Ageliki; Latsios, Georgios; Dri, Eirini; Aggeli, Constantina; Tsiamis, Eleftherios; Tsioufis, Kostas
Abstract: This case report describes a 64-year-old female with history of previous intravenous drug abuse on opioid substitution treatment with buprenorphine, who presented to the emergency department with angina and electrocardiographic findings suggestive of acute coronary syndrome. Echocardiography and left ventriculography were indicative of takotsubo cardiomyopathy, probably attributed to abrupt discontinuation of buprenorphine. Opioid withdrawal leads to sympathetic hyperactivity and increased catecholamine release, which in our case triggered takotsubo cardiomyopathy presentation. <Learning objective: Buprenorphine withdrawal may precipitate takotsubo cardiomyopathy.>